Meme as political criticism towards 2019 Indonesian general election: A critical discourse analysis - Hesti Raisa Rahardi; Rosaria Mita Amalia (Studies in English Language and Education, 2019)
This study aims to investigate the memes created by Nurhadi-Aldo, a fictional presidential candidate. Data is collected from Nurhadi-Aldo’s Instagram profile. The descriptive qualitative approach was used and the sampling procedure carried out was purposive sampling. To analyze the data and to uncover the hidden values, the three-dimension analysis proposed by Fairclough (2001) was used. The first dimension was textual analysis where the textual and visual sign of the presidential memes were examined. The second dimension was the analysis of the discursive practice surrounding the production of Nurhadi-Aldo memes. And the last was the sociocultural practice analysis that deals with how Indonesian internet users reacted to this viral phenomenon. The result points out that the memes represent the visualization of public social critics toward a political condition in Indonesia. With regards to the content creator, Nurhadi-Aldo’s memes further indicate the scepticism value of Indonesian youth. These findings further confirm that the function of the meme is not limited to entertainment purpose only, but also to deliver political criticism. Hence, it is expected that the findings will give more insights into how certain values can be delivered through the use of everyday text, such as memes.